Authoritarian Modernism in East Asia - Thompson, Mark R. (Security, Development and Human Rights in East Asia,, 2019)
Following Barrington Moore Jr., this book raises doubts about modernization theory's claim that an advanced economy with extensive social differentiation is incompatible with authoritarian rule. Authoritarian modernism in East Asia (Northeast and Southeast Asia) has been characterized by economically reformist but politically conservative leaders who have attempted to learn the "secrets" of authoritarian rule in modern society. They demobilize civil society while endeavoring to establish an "ethical" form of rule and claim reactionary culturalist legitimation. With China, East Asia is home to the most important country in the world today that is rapidly modernizing while attempting to remain authoritarian. Mark R. Thompson is Professor and Head, Department of Asian and International Studies and Director, Southeast Asia Research Centre, City University of Hong Kong, Hong Kong SAR.